2018
DOI: 10.1007/s11769-018-0985-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Changes of Croplands Between North Korea and South Korea During 1990–2015

Abstract: Studies on long-term change of cropland is of great significance to the utilization of land resources and the implementation of scientific agricultural policies. The Korean Peninsula, adjacent to China, plays an important role in the international environment of Northeast Asia. The Korean Peninsula includes South Korea and North Korea-two countries that have a great difference in their institutions and economic developments. Therefore, we aim to quantify the spatiotemporal changes of croplands in these two cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…The transition from croplands to forests has dominated the Korean Peninsula (Figure 7c) since the year 2000 because of efforts to restore forests in North Korea. In contrast to North Korea, the reduction in croplands and forests due to urbanization reported in South Korea [75][76][77] was inconsistent with results in the present study, which revealed this was rather a minor transition (Figure 7). As in South Korea, croplands abandonment occurred in Japan due to changes in the structure of the population, such as aging and migration from rural areas [78][79][80].…”
Section: Spatiotemporal Lclu Changes In the Easm Regioncontrasting
confidence: 99%
“…The transition from croplands to forests has dominated the Korean Peninsula (Figure 7c) since the year 2000 because of efforts to restore forests in North Korea. In contrast to North Korea, the reduction in croplands and forests due to urbanization reported in South Korea [75][76][77] was inconsistent with results in the present study, which revealed this was rather a minor transition (Figure 7). As in South Korea, croplands abandonment occurred in Japan due to changes in the structure of the population, such as aging and migration from rural areas [78][79][80].…”
Section: Spatiotemporal Lclu Changes In the Easm Regioncontrasting
confidence: 99%
“…Some studies of urbanization development have focused mainly on the transformation of economic life and public life [6], urban internal spatial structure [7], and urban economic cooperation and coordinated development [8]. Many studies of the DPRK have focused mainly on its economy [9], politics [10], agriculture [11], food security [12], land use [13], natural environment [14], and military strategic status [15]. However, relatively few studies have used remote-sensing data to reveal the grid-scale urban spatial pattern of the DPRK and compare it with other countries.…”
Section: Introductionmentioning
confidence: 99%
“…The world population is projected to reach 9.7 billion by 2050 [5], hence improved agricultural land production will be needed to meet such global demands. With the highest population growth rate, Africa is anticipated to account for more than half of the world's population between 2015 and 2050 hence resulting in escalation of per capita consumption rates [2], [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…As stated by the Food and Agriculture Organization (FAO) of the United Nations, croplands cover about 12% of Earth's ice-free land [2], [4]. Foley et al [2] and Gibbs et al [3] at some point indicated that agriculture was expanding mainly in the tropics, where about 80% of the new croplands were predicted to be substituting forests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation